Les moulins à farine du Séminaire de Saint-Sulpice à Montréal (1658‑1840) : essai d’analyse économique d’une prérogative du régime seigneurial - Beutler, Corinne (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1983)
AbstractThe Sulpician seminary in Paris established a Canadian chapter in Ville-Marie (later Montreal) in 1657; six years later this branch became seigneur for three properties, the seigneuries of Ile de Montréal, Lac-des-Deux-Montagnes to the northwest and Saint-Sulpice to the northeast. The Conquest severed the connection with the founding house, but until the commutation of seigneurial tenure in 1840, the Canadian seminary vigorously maintained its traditional role. While earlier work has explored the seigneurial system in its legal, social and political dimensions, little work has been done on the seigneury as an economic entity, its potential for profit and loss and the manner in which traditional obligations were balanced against financial realities. Though they do not provide a complete account and offer many difficulties for analysis, the carefully preserved records of the Séminaire de Saint-Sulpice offer an important look at the financial workings of one aspect of a seigneury. Elsewhere the author has surveyed the wheat economy of Montreal, and the place of the Séminaire in provisioning the city. In this essay, she examines the interplay of economics and politics, of obligations and profitability in the management of the resources of these three properties.The author concludes that the Sulpicians attempted to achieve two objectives simultaneously: the maintenance of status and power within the political system, and the maximization of profit within the economic system. The extensive statistical basis for her conclusions is presented in a series of tables which detail the construction of both water and wind mills, and the duration of their activity; the cash receipts from each; the annual production of the mills; the accounts receivable compared with the actual receipts; the costs of running the mills, and the profitability of the mills as a strictly economic enterprise. The Séminaire invested large amounts in both their wind, and the more expensive water mills; they expected that investment to yield a solid return. Their record of repairs and renovation to existing mills, their concern for fire prevention and their willingness to invest in greater mechanization all point to a commitment to the mills as an economic enterprise. The Séminaire jealously guarded its seigneurial rights over mill sites to the end, but by the 1820s they were prepared to concede to entrepreneurs the risk of operating in an increasingly competitive commercial and industrial climate.